P Pelatihan Penerapan Sistem Administrasi DigitalPada Masyarakat Desa Talang Donok Kecamatan Bang Haji Kabupanten Bengkulu Tengah Berbasis Aplikasi Google Form - Susanto, Yohanes; Wita Hairani; Erlian Dwisnu (Bengkulu Institute, 2024)
The Village Government of Talang Donok, Bang Haji District, Central Bengkulu Regency, still relies on a manual system, where residents must come directly to the village office to process document submissions. The implementation of digital technology to support more efficient correspondence distribution will improve the quality of public services. By using a digital system, residents no longer need to visit the village office to fill out personal data or submit requests. The socialization efforts are very useful for the residents of Talang Donok Village in understanding how to fill out the Google Form that has been provided by the village officials. The use of online administration makes it easier for residents to submit required documents anytime and anywhere. The community has responded positively to the use of online technology for document submission. Updates to the Google Sheet allow for adjustments to document numbers according to the most recent data. It is expected that after the socialization, the community's enthusiasm for the online administrative system will increase. The use of an online system in public services provides convenience, flexibility, and enhances the community's understanding of the technology applied in village administration.